A glance of the blood stage transcriptome of a Southeast Asian Plasmodium ovale isolate. - Awtum M Brashear; Wanlapa Roobsoong; Faiza A Siddiqui; Wang Nguitragool; Jetsumon Sattabongkot; Margarita M López-Uribe; Jun Miao; Liwang Cui (Public Library of Science (PLoS), 2019)
Plasmodium ovale accounts for a disproportionate number of travel-related malaria cases. This parasite is understudied since there is a reliance on clinical samples. We collected a P. ovale curtisi parasite isolate from a clinical case in western Thailand and performed RNA-seq analysis on the blood stage transcriptomes. Using both de novo assembly and alignment-based methods, we detected the transcripts for 6628 out of 7280 annotated genes. For those lacking evidence of expression, the vast majority belonged to the PIR and STP1 gene families. We identified new splicing patterns for over 2500 genes, and mapped at least one untranslated region for over half of all annotated genes. Our analysis also detected a notable presence of anti-sense transcripts for over 10% of P. ovale curtisi genes. This transcriptomic analysis provides new insights into the blood-stage biology of this neglected parasite.